TEACHING ENGLISH USING MATERIALS AT MADRASAH TSANAWIYAH NEGERI MODEL MAKASSAR - hanafi pelu (BDK Makassar, 2019)
This study aims at portrying and describing the way the English Teachers of MTsN Model Makassar conduct the learning-teaching process in the clasroom used instructionals materials. This is a descriptive with qualitative research design. The subjects of the study are English teachers, who teach in the third grade and the students of the third grade from two different classrooms. The main instrument of the study is the researcher himself. In completing the data, interview guide, and field-notes are used. The data and sources of the data are what the teachers do in classrooms concerning the research questions. The additional data are also taken from the students by means interview and recording. The finding of the study reveals that the teachers use various sources of the instructional materials. Most of the books used cover the four language skills, they are; listening, reading, speaking, and writing. The teachers use various kinds of the instructional media